2021
DOI: 10.3390/metabo11090567
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Metabolomics in Asthma

Abstract: Asthma is a highly heterogeneous disease, but the pathogenesis of asthma is still unclear. It is well known that the airway inflammatory immune response is the pathological basis of asthma. Metabolomics is a systems biology method to analyze the difference of low molecular weight metabolites (<1.5 kDa) and explore the relationship between metabolic small molecules and pathophysiological changes of the organisms. The functional interdependence between immune response and metabolic regulation is one of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 148 publications
(173 reference statements)
0
23
0
Order By: Relevance
“…Severe asthma, one of the most common inflammatory lung diseases, is characterised by uncontrolled recruitment and activation of inflammatory cells within the airways. 2,3 The inflammation of bronchial epithelium cells and their interaction with immune cells, particularly PLT, are well documented in asthma [5][6][7]10,11,13,[15][16][17] ; and PLT activation has been demonstrated by PLT mediators release in BAL and peripheral blood from patients with severe asthma. [8][9][10][11] We investigated an airway inflammation marker expressed both by bronchial epithelium cells and by peripheral circulating PLT in an inflammatory context such as asthma, to get a better insight of inflammation onset and possible epithelial-immune cells positive loop in chronic lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe asthma, one of the most common inflammatory lung diseases, is characterised by uncontrolled recruitment and activation of inflammatory cells within the airways. 2,3 The inflammation of bronchial epithelium cells and their interaction with immune cells, particularly PLT, are well documented in asthma [5][6][7]10,11,13,[15][16][17] ; and PLT activation has been demonstrated by PLT mediators release in BAL and peripheral blood from patients with severe asthma. [8][9][10][11] We investigated an airway inflammation marker expressed both by bronchial epithelium cells and by peripheral circulating PLT in an inflammatory context such as asthma, to get a better insight of inflammation onset and possible epithelial-immune cells positive loop in chronic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Asthma, which affects 358 million people around the globe and causes 495,000 deaths each year, is characterised by the recruitment, survival and activation of inflammatory cells occurring within the airways, and is associated with structural airway abnormalities. 2,3 Human bronchial epithelium cells (HBEC) play a main role in immune cells response. Among these, platelets (PLT), anucleate cells implicated in haemostasis and in inflammation, [4][5][6] appear to have a preferential interaction with lung tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional prediction also consistently showed that metabolic and degradation-related pathways were markedly enriched in our model. Additionally, beta-alanine and toluene were both reported related with airway obstruction or asthma development ( Wang et al, 2021 ), which might be an indication for our further mechanism exploration. Thus, the changes we noted in mice neonatally infected with S. pneumoniae suggest long-lasting disruption of gut microbiota by bacterial respiratory infection, and may correlate with health conditions in later life.…”
Section: Discussionmentioning
confidence: 82%
“…In-depth metabolomic and proteomic analyses of samples from asthma patients have been assessed in a broad range of tissues including blood, urine, solid tissue biopsies, exhaled breath condensate (EBC), bronchoalveolar lavage fluid (BALF), sputum, and stool, showing distinct differential associations of proteins and metabolites with disease states ( Table 2 : Significant targets resulting from Metabolic and Proteomic studies in Asthmatic Patients). At a high-level view, the associations observed to correlate with asthma reflect those of general stress response mechanisms and involve both immune and inflammatory functions ( 144 , 145 ), with many of the biomarkers identified, reflecting diverse inflammatory pathologies, which can be used to stratify asthma phenotypes and endotypes ( 146 ).…”
Section: Metabolomics and Proteomics Profiling In Asthmaticsmentioning
confidence: 99%